Relações filogenéticas entre os táxons basais da família Trichomycteridae (Siluriformes : Loricarioidea) - Lima, Sérgio Maia Queiroz (2004)
The phylogenetic relationships of the family Trichomycteridae, according to the most recent topology, appears as a tritomy at the base of the cladogram, involving the subfamilies Copionodontinae, Trichogeninae and the remaining Trichomycteridae. The aim of this study is to test the phylogenetic position of the basal Trichomycteridae subfamilies Copionodontinae and Trichogeninae, based on new morphological characters and bibliography. After cladistic analysis (length = 117; consistency index = 0.75; retention index = 0.78) of 63 characters, among 12 terminal taxa, is evident that Copionodontinae and Trichogeninae form a monophyletic group, based on 13 sinapomorphies. These are: elongate metapterygoid, with the contact area with the quadrate equal to the hyomandibula; elongate process on articular portion of the hyomandibula; hypohyal elongate; posterior extremity of the dentary truncate; 11-13 pectoral-fin rays; presence of a laminar process on the external portion of the cleithrum; elongate process on internal portion of the cleithrum angular; well developed lateral ethmoid; Weber complex weakly ankylosed to neurocranium; presence of a process anterolateral corner of the first hypobranchial; enlarged subtemporal fossa, which renders the pterotic hollow in ventral view; and elongation of the hypurapophyses of the caudal skeleton. Based upon the new phylogenetic hypothesis, a new classification for the basal Trichomycteridae subfamilies is here proposed, in which Copionodontinae is considered a junior synonym of Trichogeninae.